THE EARLY MARRIAGE AMONG THE FARMING COMMUNITY - Arropi Opi (Sosioglobal, 2018)
ABSTRACTThis article focuses on early marriage among the farming community. Marriage is a social institution that is recognized in every society. Marriage at a young age is a marriage performed by young couples under the age of 21. The purpose of this study is to find out what factors cause early marriage among the farming community and know the negative positives of early marriage. The method used is a qualitative method using an interactive model data analysis consisting of four components, namely Data Collection, Data Reduction, Data Presentation and Conclusion Withdrawal. The results of the study state that the factors that cause early marriage among the farming community are 6 factors: (1) Education. (2) Biology. (3) Pregnancy Before Marriage. (4) Understanding of Religion. (5) Economy. (6) Customs and Culture.keywords : For Young Marriage, Factors, Farmer Community.